1992
DOI: 10.1105/tpc.4.11.1359
|View full text |Cite
|
Sign up to set email alerts
|

Functional homologs of the Arabidopsis RPM1 disease resistance gene in bean and pea.

Abstract: We showed that a bacterial avirulence (avr) gene function, avrPpiA1, from the pea pathogen Pseudomonas syringae pv pisi, is recognized by some, but not all, genotypes of Arabidopsis. Thus, an avr gene functionally defined on a crop species is also an avr gene on Arabidopsis. The activity of avrPpiA1 on a series of Arabidopsis genotypes is identical to that of the avrRpm1 gene from P.s. pv maculicola previously defined using Arabidopsis. The two avr genes are homologous and encode nearly identical predicted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 62 publications
4
55
0
Order By: Relevance
“…Although Arabidopsis ecotype Col-0 can elicit ETI in response to both AvrRpm1 and AvrRpt2, the observed HR is known to be a consequence of perception of the latter by RPS2 [34]. Each of the tested nopB ::Δ 79avrRpt2 gene fusions were sufficient for Pto DC3000 to trigger an HR at 20hpi, confirming that this family encodes bona fide T3Es (Figure 2B).…”
Section: Resultsmentioning
confidence: 64%
“…Although Arabidopsis ecotype Col-0 can elicit ETI in response to both AvrRpm1 and AvrRpt2, the observed HR is known to be a consequence of perception of the latter by RPS2 [34]. Each of the tested nopB ::Δ 79avrRpt2 gene fusions were sufficient for Pto DC3000 to trigger an HR at 20hpi, confirming that this family encodes bona fide T3Es (Figure 2B).…”
Section: Resultsmentioning
confidence: 64%
“…This response involves an increased production of defense-related proteins such as cysteine proteases, thaumatin-like proteins, chitinases, superoxide dismutase, peroxidases and catalase in the host plants [7]. Additionally, plant-microbe interactions also involves host-to-microbe specific responses in a gene-for-gene manner, whereby a specific pathogen-derived avirulent ( Avr ) protein is recognized by a specific plant resistant ( R ) protein as the case of Pseudomonas syringae AvrRPM1 and AvrRpt2 proteins which are respectively recognized by the products of the Arabidopsis RPM1 and RPS2 resistance genes [8,9]. However, a high-throughput transcriptional analysis study of innate responses of Arabidopsis plants showed a strong overlap in the production of nonhost and host-specific proteins in the presence of flagellin, highlighting the power of high-throughput technologies in identifying overall host responses to plant pathogens while noting that understanding plant-microbe interactions is still a complex subject [10].…”
Section: Introductionmentioning
confidence: 99%
“…vesicatoria (Casper-Lindley et al 2002), and the cya domain from cyclosin gene of Bordetella pertussis (Sory and Cornelis 1994) cloned as Cya expression cassette in the broad-host-range vector pVSP61 (Loper and Lindow 1987). pVSP nPro+AA1-89-AvrRpm1:Cya contains the AvrRpm1 promoter (189 nt) and the first 267 nt of AvrRpm1 (Dangl et al 1992;Rentel et al 2008) fused to the cya domain. pEDV5 (Sohn et al 2007), containing the AvrRps4 promoter (129 nt), a 5′ coding region (411 nt), an HA tag (27 nt), and a multiple cloning site (MCS) (including ClaI), was provided by J. Jones (Sainsbury Laboratory, Norwich, U.K.).…”
Section: Plasmid Vectors Used and Constructedmentioning
confidence: 99%